Growing a Digital Literature Culture for Students in the History Education Department Faculty of Teacher Training and Education Lambung Mangkurat University - Fitri Mardiani; ‪Mohamad Zaenal Arifin Anis; Mohamad Dody Hermawan; Cucu Widaty (Social Studies Conference Proceedings, 2021)
The era of the industrial revolution 4.0 is an era of information technology developing rapidly in education. This is getting stronger when the COVID-19 pandemic has hit this nation since the beginning of 2020. Facing the challenges of life in the era of the industrial revolution 4.0, the role of the historical education study program is critical, especially in the development of science and technology. Therefore, history learning is demanded to be able to enter into a new order following its primary goal of being a reference and foothold in navigating the future from the results of studying past life values. First, the research aims to describe historical learning in the digital era. Second, describe the development of digital learning resources in history learning through a qualitative descriptive method consisting of data collection, data reduction, and presentation of conclusions and verification through data triangulation. The research subjects consisted of 100 students from classes 2018, 2019, and 2020. This phenomenon was analyzed to understand the role of digital literacy in historical learning resources in the digital era. The results of this study indicate that the initial step of having digital literacy skills is constructive in navigating life in the industrial era 4.0 to prepare themselves for the overwhelming flow of information and provide guidance for students in accessing, selecting, and utilizing credible and targeted information, especially for implementation—distance learning during the pandemic which refers to self-reliance and personal creativity.